Abû 'l-Maḥāsin ibn Taghrî Birdî's annals - İbn Tağrîberdî, 1410-1470. (Berkeley Berkeley Berkeley Berkeley Berkeley)
<5> cilt (2. c. 534, l sayfa ; 3. c. 130, iv sayfa ; 5. c. 840, xli sayfa ; 6. c. 993, lxxii sayfa ; 7. c. 967, lvi sayfa)